Interrogating the scope and extent of punitive measures in the public procurement legal regime of the Zimbabwean energy sector - Gonditi, Tafadzwa Nathaniel (Midlands State University, 2020)
Public procurement refers to the acquisition of goods, services and works by a procuring entity using public funds . Globally, public procurement occupies a key role in service delivery and performance of government departments and public entities. Over and above the fiduciary obligation of a particular government administration to deliver goods and services to citizens, public procurement is essential for the execution of public contracts . For most developing countries, especially in Africa, public procurement is a critical yardstick in measuring government efficiency. This is because governments in these countries are the major drivers for economic growth and development, and perhaps the most important determinant in the acquisition and consumption of public services . In Zimbabwe the current laws regulating public procurement, particularly tender awarding, have been nothing short of scandalised by the behaviour and conduct of public officials and institutions responsible for them. This is due to the rampant corruption marring the tender system, particularly in the energy sector, where various scandals have been reported inextricably tying senior government officials to graft in this sector. As a result this has caused the government to lose millions of dollars in revenue each year. The energy sector is essential to Zimbabwe’s trade, industry and societal development. Its proper regulation or lack thereof has grave impacts on any efforts by the country to effectively turnaround the economy and to achieve sustainable growth. For instance, Zimbabwe’s electricity power requirements are partly fulfilled through local generation supplemented by 35% (300MW) imports from neighbouring countries that include South Africa, Mozambique, Zambia and the Democratic Republic of Congo . The country is experiencing a crippling energy crisis, largely due to poor maintenance of the existing ageing plant presumably worsened by delays in replacement of obsolete spares among other factors.